Analisis Pengaruh Bukaan Pada Dinding Geser Pelat Baja - Nidiasari, Nidiasari (Universitas Andalas, 2025)
Steel plate shear walls are structural elements that can increase lateral capacity due to earthquake loads. In certain conditions, the presence of openings such as doors and windows is often avoided in shear wall areas because they have the potential to interfere with the performance of the shear wall plate. If there is limited area for openings due to needs or architectural reasons, the shear wall area can be used as an alternative. This study aims to evaluate the effect of openings on shear wall plates through a finite element-based numerical study. There are three test specimen models, two of which are plates with openings and one test specimen is a full plate used as a comparison. Loading is given statically monotonically until it reaches a displacement of 40 mm, or equivalent to a 4% drift. The analysis results show that openings significantly reduce the plate's capacity to withstand lateral loads by more than 50%.